A94 SHIP-MICROBIOME INTERACTIONS IN INTESTINAL INFLAMMATION. (1st March 2018) - Dobranowski, P; Menzies, S; Sly, L M
Abstract: Background: Immune regulating Src homology domain 2-containing inositol phosphatase (SHIP) protein levels and activity are reduced in patients with the chronic intestinal inflammatory condition, Crohn's disease (CD). SHIP deficient ( -/- ) mice develop spontaneous CD-like ileal inflammation beginning at 4 weeks of age. Several groups have associated the microbiome with the pathogenesis of CD, where the loss of other immune regulating genes such as NLRP6, NLRP12, and NOD2 result in microbial population changes and intestinal inflammation in mice. However, the microbiome of SHIP -/- mice has not been examined. Aims: To investigate whether SHIP attenuates ileal inflammation by maintaining microbial diversity and protective commensal populations. Methods: Bacterial DNA was extracted from stool and colonic, cecal, and ileal contents of SHIP -/- and SHIP +/+ mice at 4 and 8 weeks of age. Bacterial load was quantified by qPCR and normalized by 16S rrn gene copy number. V4-V5 hypervariable regions of the 16S rRNA gene were sequenced with the Illumina MiSeq platform and fastq files were imputed using QIIME 1.9. Microbial diversity metrics and relative abundance measures were generated with data rarefied to 5500 sequences per sample. Abundance measures were normalized by rrn gene copy count. Metabolomic data were obtained by PICRUSt v1.1.1 and directly measuring short chain fatty acid concentrations of ileal contents using gas chromatography. Results: Bacterial DNA was extracted from a total of 94 samples. No significant differences were observed in bacterial loads between age and genotype groups, indicating that ileal inflammation in SHIP -/- mice is not associated with bacterial overgrowth. Reductions in microbial alpha-diversity were seen in 8 week old SHIP -/- microbiomes as measured by number of OTUs and chao1. Separation of clusters were seen between 8 week old SHIP -/- and SHIP +/+ during principle component analysis, but not at 4 weeks old. 8 week old SHIP -/- microbiota showed reductions in the unclassified Bacteroidetes family S24-7. Non-significant changes in abundances were seen at the genus-level. Reduced amino acid metabolism and elevated glutathione and lipid metabolism in 8 week SHIP -/- samples were predicted with PICRUSt, consistent with other models of intestinal inflammation. Modest reductions in butyric acid and propionic acid and elevations in branched chain fatty acids were found after the onset of inflammation. Conclusions: Significant changes in bacterial diversity, populations, and metabolism were only observed after the onset of inflammation. Similar but non-significant changes to the microbiome were observed prior to the onset of inflammation. Taken together, these results suggest that SHIP deficiency is sufficient to drive changes in the intestinal microbiome, which may contribute to, and are amplified by intestinal inflammation. Funding Agencies: CIHR